Linguistic and Pragmatic Study of Word Combinations with Coronamic Elements in Modern Linguistics (Texas Journal of Philology, Culture and History, 2023)
This article provides general concepts of pragmatics, linguistic and pragmatic study of word combinations with coloronymic elements in modern linguistics.